Influence of sports groups on the risk of stress urinary incontinence in sportswomen - Selecka, Michaela; Hagovska, Magdalena; Bukova, Alena; Svihra, Jan (European journal of obstetrics, gynecology and reproductive biology, 2021)
OBJECTIVES: To evaluate sports groups on the risk of stress urinary incontinence (SUI) in sportswomen and its impact on their quality of life. STUDY DESIGN: Cross-sectional study. The group consisted of 249 sportswomen with a mean age of 22.18 ± 6.11 years. We used the International Physical Activity Questionnaire (IPAQ), the International Consultation on Incontinence Questionnaire (ICIQ-UI), the Overactive Bladder Questionnaire (OAB-q) and the Quality of Life Assessment Questionnaire Concerning Urinary Incontinence (Contilife) were used for evaluation. We divided the sports into the following six groups: 1. Functional mobilization sports (FMS); 2. Strength sports (SS); 3. Aesthetic-coordination and sensory-concentration sports (ACS); 4. Heuristic-individual and martial arts (HIS + MAS); 5. Heuristic-collective sports with a hockey stick (HCS-A); and 6. Heuristic-collective sports with a ball (HCS-B). RESULTS: The symptoms of SUI according to the ICIQ-UI SF were 1.80 ± 2.93. The estimate of the relative risk (OR) of developing SUI was most significant in the FMS group (OR = 1.96, 95% CI: 1.04-3.68; p < 0.03). Other sports groups did not pose a significant relative risk of developing SUI and had a lower incidence of SUI. In SS was OR = 0.77, in EKS, OR = 0.69, in (HIS + BS), OR = 1.26, in (HKS-A) was OR = 0.63, in (HKS-B) was OR = 1.02. There were no significant differences between the groups in the overall score of the Contilife, which assesses quality of life. CONCLUSION: The Functional mobilization sports group had a 1.96 times higher risk of SUI compared to that in other sports groups.
Keywords: kvalita života; Adult; mladý dospělý; inkontinence moči; dospělí; Urinary Incontinence; mladiství; průzkumy a dotazníky; Young Adult; Adolescent; Cross-Sectional Studies; Humans; lidé; průřezové studie; stresová inkontinence moči; Surveys and Questionnaires; Urinary Incontinence, Stress; Quality of Life